Understanding Aging, Frailty, and Resilience in Ontario First Nations. Issue 3 (15th September 2021) - Slater, Morgan; Jacklin, Kristen; Sutherland, Roseanne; Jones, Carmen; Blind, Melissa; Warry, Wayne; Valvasori, Meghan; Walker, Jennifer
ABSTRACT: Following Canadian estimates of frailty, academic researchers and the Chiefs of Ontario came together to create the first Ontario-wide profile of aging in First Nations people in Ontario. Using self-reported data from First Nations adults who participated in the Ontario First Nations Regional Health Survey Phase 2, we found that First Nations people in Ontario experience higher rates of frailty than the general Canadian population and early onset frailty appears to affect First Nations communities. This is important to consider as communities plan for health care needs of an aging population and is particularly relevant in the face of Covid-19, as we know severity is exacerbated by underlying health conditions.